Neurocranial anatomy of Sus arvernensis (Suidae, Mammalia) from Collepardo (Early Villafranchian; central Italy): taxonomic and biochronological implications. (2nd January 2022) - Iannucci, Alessio; Bellucci, Luca; Conti, Jacopo; Mazzini, Ilaria; Mecozzi, Beniamino; Sardella, Raffaele; Iurino, Dawid Adam
ABSTRACT: Suidae remains recovered from the late Pliocene site of Collepardo (Latium, central Italy) are described and assigned to Sus arvernensis, a small-sized Ruscinian to Early Villafranchian (MN14-MN16a) species. In Italy, S. arvernensis only occurs in the Triversa Faunal Unit (MN16a), supporting the recently revised chronology of Collepardo. CT-scan methods are used to virtually extract and analyse a newly discovered neurocranium, providing the content for the first inner cranial description carried out on an extinct Suidae. Our analysis reveals that S. arvernensis has an anteroposteriorly elongated and dorsoventrally flat cerebrum, similar to that of the Asian Babyrousa babyrussa and the African Hylochoerus meinertzhageni . These species substantially differ in size and are representatives of two widely diverging phylogenetic clades, excluding relatively simple evolutionary or allometric explanations for brain morphology in Suidae.